The implementation of the Local Economic Development Strategy by the Greater Tzaneen Municipality in Limpopo - Malele, Lebogang Ernest (My University, 2018)
The aim of this study is to investigate and assess the effectiveness of Greater Tzaneen Municipality in implementing LED strategies in rural communities. Although the concept of Local Economic Development has been studied and widely debated in South Africa, the present study intends to determine the extent to which the implementation of LED strategy by Greater Tzaneen Municipality contributes towards improving the livelihood of communities for sustainable local economic development. In other words, the study purports to develop a more holistic understanding of the dynamics of local economic development efforts. This is a mixed method study in which elements of qualitative and quantitative approaches to collect, analyze, validate and interpret data were used. Quantitative design was used to profile respondents and do some statistical analysis of the population. The quantitative design used was in the form of a semi-structured survey questionnaire to acquire statistical data. Since the study is heterogeneous, stratified random sampling was used for the quantitative design whereby ward councillors, ward committees, project leaders and community stakeholders (n= 60) participated. For the qualitative aspect of the study face-to-face interviews schedule was used in order to construct the reality from the interviewees‟ world and to gain more in-depth dynamics and complexities by virtue of being the more natural form of interaction with respondents. Key municipal officials directly involved in LED and those who have more knowledge and information concerning LED implementation were identified by means of purposive sampling technique (n=10). The findings revealed that even though Greater Tzaneen Municipality on average is on the implementation side, there are some factors that hinder it from achieving the 100% LED strategy implementation. Even though policies are in place, it appears like LED strategies have produced very few success stories for various reasons country wide which among others includes lack of capacity within municipalities, financial constraints and poor and incorrect implementation. The other challenge is that communities regard LED as employment creation by municipalities and should not be viewed only as creating economic benefits, but as playing a vital role in poverty alleviation and therefore should have a strong social focus. As per the constitutional mandate Section 152 (1), (2) and Section 153 LED should be an integral part in the planning activities of municipalities across departments and not be afterthought. The process should clearly reflect participation by all wards and their respective communities, local economic growth, poverty alleviation and job creation as well as prioritizing human development initiatives.
Thesis (M.Dev.) --University of Limpopo, 2018
Keywords: Economic development strategy; Greater Tzaneen Municipality; Poverty alleviation; Job creation; Agricultural development projects; Economic development projects -- Law and legislation.; Economic development - South Africa